Understanding foreign language writing anxiety and its correlates - Li, Rui (Frontiers in Psychology, 2022)
Despite the growing body of studies that investigated foreign language writing anxiety and its correlates, there is still a dearth of comprehensive meta-analysis regarding the effect sizes of these studies. To this end, this study identified 84 effect sizes from 22 primary studies to calculate the aggregated correlation between foreign language writing anxiety and several key high- and low-evidence correlates. For the two high-evidence correlates, moderator analyses were also conducted, which demonstrated that foreign language writing anxiety has a moderate correlation with foreign language writing performance and foreign language writing self-efficacy. The three low-evidence correlates have positively moderate effects of foreign language speaking anxiety, foreign language listening anxiety and foreign language reading anxiety. Learners’ age and language proficiency were found to be significant moderators for some correlations. Implications of the results were discussed as well.